ENCAPSULATION OF INDONESIAN PROPOLIS BY CASEIN MICELLE - MUHAMAD SAHLAN; TONY SUPARDI (International Journal of Pharma and Bio Sciences, 2013)
Propolis is strong adhesive material with one of most valuable bees product and has wide range of biological activities such as antibacterials, antiviruses, antifungals, anti-inflammation, photoprotector and so on. Propolis has been aplied as antimicrobials agent in food and healtcare products. To improve handling properties, Indonesian propolis were encapsulated by casein micelle with a homogenizer followed a sonication, and separated by micro- and ultra-filtration system, created micro- and nano- particles. These micro- and nano-particles exhibited high flavonoids and moderate polyphenols capacities (encapsulations efficiency, 94% and 67% for flovonoids and polyphenols, respectively) Size of particles was analyzed by particle size analyzer (PSA) showed that the average size of particles are 1,3 micrometer and 300 nanometer. The morphologies of particles analyzed by transmission electron microscopy (TEM). The results also shown that encapsulated Indonesian propolis have antibacterial activity. Therefore, these micro- and nano-propolis might be used as antimicrobials agent or others in food or healtcare products.